Demonstration of the Enhanced Disinfection of E. coli Water Contamination by Associated Solar Irradiation with Potassium Persulfate - Ghader GHANIZADEH; Ali NASERI ARA; Davoud ESMAILI; Hossein MASOUMBEIGI (Tehran University of Medical Sciences, 2015)
Background: Tremendous amount of researches have investigated the issue of water photodisnfection. The aim of this research is to illustrate the influences of bacterial density, turbidity, exposure time and potassium persulfate (KPS) dosage on the efficacy of associated solar disinfection (SODIS) with KPS for E. coli (ATCC: 25922) eradication as an efficient and inexpensive process. Methods: Desired bacterial density and turbidity was achieved by spiking of 0.5 Mc Farland (1.5×108 cell/ml) and sterile soil slurry in 1 liter of the commercially bottled water. Results: The highest value of UVA solar irradiation measured at 13.30 p.m was 5510 µW/Cm2. Increase of bacterial density from 1000 to 1500 cell/ml led to an increase in disinfection lapse time, except in 2 mMol/l KPS. Spiking of 0.1 mMol/l of KPS was not effective; however, increase of KPS dosage from 0.1 mMol/l to 0.7, 1.5 and 2 mMol/l led to the enhancement of disinfection time from 4 h to 3 h and 1 h, respectively. For bacterial density of 1000 cell/ml, increasing KPS dosage up to 0.7 mMol/l had no improved effect; however, beyond this dosage the disinfection time decreased to 1 h. Without KPS and up to 150 NTU within 4 h exposure time, E. coli disinfection was completed. In 2 mMol/l KPS and 1000 and 1500 cell/ml, the 2 h contact time was sufficient up to 150 and 100 NTU, respectively; moreover, complete disinfection was not achieved at higher turbidity. Conclusion: Association of KPS with SODIS can lead to decreasing of water disinfection time.   Keywords: Disinfection, Solar irradiation, Potassium persulfate, Water, E. coli